Sex-specific differences in abscopal responses to combined radiotherapy and immune checkpoint inhibition–insights from a multicenter study - Trommer, Maike; Rühle, Alexander; Ehret, Felix; Lamrani, Allison; Schmitter, Charlotte; Kaufmann, Justus; Mäurer, Matthias; Wurschi, Georg; Jiang, Ping; Baehr, Andrea; Hardt, Annika; Bodensohn, Raphael; et al. (Frontiers in Immunology, 2026)
PurposeAbscopal effects (AbE) during combined radiotherapy (RT) and immune checkpoint inhibition (ICI) represent a potential mechanism for systemic tumor control, yet sex-specific differences in these responses remain largely unexplored. We investigated sex-associated signals in outcomes of combined RT-ICI in a multicenter cohort. We analyzed the incidence of AbE and survival outcomes with respect to clinical and biomedical markers.MethodsIn this observational multicenter study, patients with metastatic solid tumors receiving RT-ICI and showing at least one non-irradiated lesion (NIL), assessed using iRECIST criteria, were analyzed. Abscopal response (AR) was defined as ≥30% reduction in NIL size, abscopal progression (AP) as ≥20% increase, and abscopal control (AC) as changes within this range.ResultsAmong 3,773 screened patients, 142 met the inclusion criteria (62% male, median age 62 years; 38% female, median age 58 years). AR and AC occurred more frequently in females (24% vs. 14%, 35% vs. 31%). While OS showed no significant difference (p=0.81), Cox regression analyses revealed significant associations of a longer ICI-to-RT-interval (males: HR = 0.903 [0.833–0.978], p=0.012; females: HR = 0.748 [0.621–0.900], p=0.002) and a BMI ≥25 kg/m² with survival in both sexes (males: HR = 4.282 [1.473–12.446], p=0.008; females: HR = 4.801 [1.182–19.502], p=0.028 with survival in both sexes). Elevated C-reactive protein (CRP) (≥5 mg/L) showed prognostic significance only in males (HR = 4.764 [1.184–19.170], p=0.028).ConclusionOur findings suggest the possibility of sex-specific patterns in AbE occurrence. Additionally, our analyses identified sex-associated prognostic factors, including the importance of ICI-to-RT interval and BMI in both sexes and the male-specific prognostic value of CRP. These observations warrant further research and consideration in designing personalized RT-ICI combination strategies.